Investigation of Grain Formation Mechanism in CuAl Shape Memory Alloy By Molecular Dynamic Simulation - Ozgen, S.; Orhan, O.; Canbay, C. Aksu; Brazolin, G. F.; Silva, R. A. G. (Amer Inst Physics, 2018)
A good understanding of grain formation mechanisms during the solidification of shape memory alloys is an important task for characterization of these alloys. In this study, the grain formation mechanism of the Cu-at. 19.9Al shape memory alloy was investigated using molecular dynamics simulations. To realize the simulation study, a cube-shaped model with L12 super-lattice structure and cell size of 5.47 nm was created. Simulation studies in which, the physical interactions between atoms are represented by Cai and Ye version of the embedded atom method (EAM) were performed with LAMMPS software. The model was melted by heating from 300 K to 2500 K and solidified by cooling from 2500 K to 300 K. Melting temperature of the alloy was determined by thermodynamic analysis, bound angle analysis (BAA) and adaptive common neighbor analysis (ACNA). All of these analysing methods were used for structural investigations. As a result, it has determined that the experimental results of the crystal structure of the alloy were in accordance with the simulation results.
34th International Physics Congress (IPS) of the Turkish-Physical-Society (TPS) -- SEP 05-09, 2018 -- Konacik, TURKEY
Keywords: Homogeneous Nucleation